Efficacy and safety of an intraoral electrostimulation device for xerostomia relief: a multicenter, randomized trial (2011)
To evaluate the efficacy and safety of an intraoral electrostimulation device, consisting of stimulating electrodes, an electronic circuit, and a power source, in treating xerostomia. The device delivers electrostimulation through the oral mucosa to the lingual nerve in order to enhance the salivary reflex. The device was tested on a sample of patients with xerostomia due to Sjögren's syndrome and other sicca conditions in a 2-stage prospective, randomized, multicenter trial. Stage I was a double-blind, crossover stage designed to compare the effects of the electrically active device with the sham device, each used for 1 month, and stage II was a 3-month open-label stage designed to assess the long-term effects of the active device. Improvement in xerostomia severity from baseline was the primary outcome measure. A total of 114 patients were randomized. In stage I, the active device performed better than the sham device for patient-reported xerostomia severity (P<0.002), xerostomia frequency (P<0.05), quality of life impairment (P<0.01), and swallowing difficulty (P<0.02). At the end of stage II, statistically significant improvements were verified for patient-reported xerostomia severity (P<0.0001), xerostomia frequency (P<0.0001), oral discomfort (P<0.001), speech difficulty (P<0.02), sleeping difficulty (P<0.001), and resting salivary flow rate (P<0.01). Our findings indicate that daily use of the device alleviated oral dryness, discomfort, and some complications of xerostomia, such as speech and sleeping difficulties, and increased salivary output. The results show a cumulative positive effect of the device over the period of the study, from baseline to the end of the trial.